Compact, Energy Efficient Simultaneous Transmission of Analog and Different Digital Signals With a Single Ring Modulator - Mohamed I. Hosni; Younus Mandalawi; Janosch Meier; Ahmed H. Elghandour; Linjie Zhou; Thomas Schneider (IEEE Photonics Journal)
We present a compact, agnostic transmitter capable of simultaneously transmitting all types of signals (analog and digital with different modulation formats) with a single-ring modulator with a radius of 10 micrometers and a bandwidth of around 18 GHz. To the best of our knowledge, we show for the first time, experimental results for transmitting three different Nyquist BPSK signals with an aggregated baud rate of 24 GBd in such a compact device. Additionally, we show the simultaneous transmission of a 3 GHz analog signal together with normal and Nyquist-shaped 4 GHz BPSK signals. All results were achieved without any power-consuming pre- or postprocessing to adapt the signals to the transfer function of the modulators. The simultaneous transmission of analog and digital signals in a device with a small footprint and low power consumption may be especially advantageous for future access networks.